A Calculation Approach of Embodied Energy, Carbon Emission and Eco-Costs on Waste Recycled Composite Materials - Siswanti Zuraida (Tamkang University Press, 2021)
The issue of waste recycling has recently become a major topic of research, particularly regarding building material technology. From the subject, numerous studies discussed recycling waste into building components, for instance, wall panels, mixed concrete material, concrete bricks, etc. Nevertheless, it brought another environmental issue due to the use of cement as the major ingredient. The cement production process is releasing carbon emissions that have a negative impact on the environment. The recycled materials that are used as concrete components also, from their basic form, have a negative impact on the environment. Disposable diapers and plastic PET are non-degradable materials that are hard to demolish. The paradox has created pros and cons, especially in environmental impact-based research. This study gives a calculation approach in determining the environmental impact using the manual database. It employs several environmental impact indicators such as embodied energy (EE), carbon emissions (CE) that come out during the manufacturing process of the composite material product, and the environmental costs called eco-cost (EC) as the key indicators. Three types of waste concrete materials were analyzed, such as disposable diapers concrete, PET concrete, and shredded wood-concrete. The result showed in terms of EE, material manufacturing is very important to decrease the EE. The material selection that has lower EE is important to reduce EE in the building. Additionally, the result showed the beneficial environmental impact in terms of CE and EC, the waste materials could reduce the impact due to recycling credit that applies to the process.